![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
因式分解:①-6(2a-b)2-4(b-2a)2②6(x+y)2-2(x-y)(x+y)③-3(x-y)2-(y-x)3④3a(m-n)-2b(
因式分解:①-6(2a-b)2-4(b-2a)2②6(x+y)2-2(x-y)(x+y)③-3(x-y)2-(y-x)3④3a(m-n)-2b(n-m)⑤9(a-b)(a...
因式分解:①-6(2a-b)2-4(b-2a)2②6(x+y)2-2(x-y)(x+y)③-3(x-y)2-(y-x)3④3a(m-n)-2b(n-m)⑤9(a-b)(a+b)-3(a-b)2⑥3a(a+b)(a-b)-2b(b-a)
展开
1个回答
展开全部
①-6(2a-b)2-4(b-2a)2
=-10(2a-b)2
②6(x+y)2-2(x-y)(x+y)
=2(x+y)[3(x+y)-(x-y)]
=2(x+y)(2x+4y)
=4(x+y)(x+2y);
③-3(x-y)2-(y-x)3
=-3(x-y)2+(x-y)3
=(x-y)2(-3+x-y);
④3a(m-n)-2b(n-m)
=3a(m-n)+2b(m-n)
=(m-n)(3a+2b);
⑤9(a-b)(a+b)-3(a-b)2
=3(a-b)[3(a+b)-(a-b)]
=3(a-b)(2a+4b)
=6(a-b)(a+2b);
⑥3a(a+b)(a-b)-2b(b-a)
=3a(a+b)(a-b)+2b(a-b)
=(a-b)(3a2+3ab+2b).
=-10(2a-b)2
②6(x+y)2-2(x-y)(x+y)
=2(x+y)[3(x+y)-(x-y)]
=2(x+y)(2x+4y)
=4(x+y)(x+2y);
③-3(x-y)2-(y-x)3
=-3(x-y)2+(x-y)3
=(x-y)2(-3+x-y);
④3a(m-n)-2b(n-m)
=3a(m-n)+2b(m-n)
=(m-n)(3a+2b);
⑤9(a-b)(a+b)-3(a-b)2
=3(a-b)[3(a+b)-(a-b)]
=3(a-b)(2a+4b)
=6(a-b)(a+2b);
⑥3a(a+b)(a-b)-2b(b-a)
=3a(a+b)(a-b)+2b(a-b)
=(a-b)(3a2+3ab+2b).
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询